Static Load Analysis of Various Wing Spar Profiles: A Comparative Study between Mathematical and Finite Element Methods - Widyawasta Widyawasta; Alief Wikarta (JMES: The International Journal of Mechanical Engineering and Sciences, 2024)
Unmanned aerial vehicles (UAVs) have become increasingly essential in both civilian and military contexts, serving various roles such as surveillance, mapping, cargo transport, and specialized tasks. The demand for long-endurance surveillance UAVs is critical for covering vast areas continuously, prompting the development of Medium Altitude Long Endurance (MALE UAV). This paper explores the structural strength analysis of various wing spar profiles of MALE UAV using mathematical analysis and Finite Element Method (FEM) under static loads. The wings, pivotal for generating lift, are subjected to rigorous operational loads, necessitating robust structural reliability. While mathematical analysis provides fundamental insights, FEM allows for detailed simulations under various conditions. Comparative studies between mathematical analysis and FEM are conducted to validate the structural strength of MALE UAV wings, with a focus on different spar profiles. Aluminum Al7075-T6 is used as the material, with convergence tests ensuring FEM accuracy. The comparative analysis highlights significant variations in normal and shear stress among different spar profiles, with the widest disparities observed at the wing root, 6.40 and 1 MPa resp., and the least, 1.51 and 0.63 MPa, close to the wing tip position at 6.75 m. These insights underscore the critical role of structural integrity in optimizing UAV performance and reliability.